Patrimonial Education And Photography: he Clic@R Iitapina Project and the Rescue of The Local Memory - Malverdes, André; Gomes Barbosa, Anderson (Guará Journal, 2019)
It analyzes heritage education actions using photographs of person-al collections as artistic language to express the cultural manifesta-tions of a community, with the purpose of verifying their relationship with the feeling of belonging to the local history and with the appreciation of their cultural patrimony. The approach of the problem occurred through quantitative research (statistical instruments) and qualitative, using deduction as a research method to evaluate the effectiveness of actions for society. It was found that the patrimonial education workshop presented relevant content and that its prod-ucts caused positive socio-cultural impacts. It was concluded that the patrimonial education methodology applied by the Clic@r Itapina project team was efficient for the purpose of awakening the sense of belonging and was a way to value the local culture. The hypoth-esis was also confirmed, because the more the access to the photo-graphs became available, the more affective feelings were aroused, bringing good memories. In the final analysis, it was verified that the information content of the photographs refers to the feeling of belonging and to the appreciation of cultural heritage.